DISCREPANCY BETWEEN PERCEIVED AND OBSERVED REALITY ABOUT THE 21ST CENTURY SKILLS IMPLEMENTATION AT PRIMARY SCHOOL - Ni Luh Made Juli Candra Ningsih; Ni Nyoman Padmadewi; Luh Gd Rahayu Budiarta (Acitya: Journal of Teaching and Education, 2021)
ABSTRACT For preparing the Indonesian students that mastering the 21st century skills, the teachers as the intermediary of the students and the government should be ready to implement each. Meanwhile, from the teachers' readiness, there might be differences between their perception and observed reality. For this reason, the study was to investigate the discrepancy between perceived and observed reality on the implementation of the 21st century skills by the English teachers at primary school. This study is needed to conduct to get real information about the teachers' readiness for implementing 21st century skills. This research had arranged in the Primary School of Tabanan regency during the English teaching and learning. Six English teachers used as the subject related to their perception and reality of the implementation of 21st century skills. A mix-method design used to collect the data with the quantitative way for teachers perceived and descriptively for observed reality. The questionnaire, observation checklist, document, and interview guide were the method for data collection. The result showed that there was a discrepancy between the teachers’ perceived and observed reality about the implementation of 21st century skills at primary school. The discrepancy was the teachers do not ready to implement the 21st century skills, but they perceived the opposed. Keywords: Discrepancy, 21st Century Skills, Teaching English, Primary School